Climate variability in agroecosystems: A quantitative assessment of stakeholder-defined policies for enhanced socio-ecological resilience. (August 2022) - Carper, Jordan M.; Alizadeh, Mohammad Reza; Adamowski, Jan F.; Inam, Azhar
Abstract: CONTEXT: The development of methods for improving the assessment of resilience of socio-ecological systems has become increasingly important as the severity and variability of global climate patterns continue to compound and intensify. OBJECTIVE: The present study was conducted with the aim of using a dynamically-coupled bio-physical and socioeconomic model to test the efficacy of stakeholder-defined policy measures in conferring resilience to two agroecological variables, farm income and water-table depth, experiencing both socio-ecological shocks and climatic stress in the Rechna Doab basin of northeastern Pakistan. METHODS: The objective was accomplished by using a dynamically-coupled physical and group-built system dynamics modelling framework for scenario testing and output generation, including three NASA Earth Exchange Global Daily Downscaled Climate Projections (NEX-DGGP), two relevant socio-ecological shock scenarios (market inflation and canal water supply variability), and three stakeholder-defined policy measures. Resilience was assessed using the following system functionality metrics: 1) The degree of return for each variable after a perturbation, i.e., the extent to which the observed variable returns to baseline functioning; 2) The return time of the variable to baseline functioning; 3) The rate of variable return to baseline; 4) Overall perturbation of the system post-disturbance; and 5) The corrective impact of the shock on system functionality. Differences in the resilience metrics were subsequently compared based on the behavioral change(s) of the study variables in response to the application of the three selected policy scenarios. RESULTS AND CONCLUSIONS: The results presented here indicate that rainwater harvesting is the most effective stakeholder-defined policy measure for improving or maintaining resilience of the tested study variables in the Rechna Doab agricultural basin; this holds true for every climate and shock scenario with the exception of water-table depth in the upper and mid-watershed regions under canal supply shock conditions, for which canal lining is the most effective policy measure. The irrigation improvement and canal lining policies were more effective in improving the resilience metrics of water-table depth than those of the farm income variable, as the water-table depth variable is not bound so tightly by economic constraints; although there were regional differences in policy efficacy, these trends hold true, on average, for the entire watershed. The results presented herein align well with previous studies conducted in the region which note similar patterns in spatial resilience of agroecosystem variables (i.e., upper to lower watershed) in the Recha Doab basin as well as regional differences in the efficacy of the stakeholder-defined policy measures. SIGNIFICANCE: This unique approach for assessing socio-environmental policies can help improve decision-making processes with respect to agro-infrastructure and climate change mitigation strategies in vulnerable agroecosystems. Graphical abstract: Unlabelled Image Highlights: Improving the resilience of socio-ecological systems has become crucial with the intensification of global climate patterns Quantify resilience of climate-stressed socio-agroecological variables via application of stakeholder-defined policies Rainwater harvesting is the most effective stakeholder-defined policy measure for achieving variable-level resilience Methods can be utilized in single-system analyses as well as comparative studies across spatial and temporal boundaries The methods used herein can help improve socio-ecological policy development and climate change mitigation strategy